2019
DOI: 10.1080/19420862.2019.1612690
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated glutamine synthetase as a selection marker in CHO cells to efficiently isolate highly productive stable cells for the production of antibodies and other biologics

Abstract: Chinese hamster ovary (CHO) cells are the biopharmaceutical industry's primary means of manufacturing therapeutic proteins, including monoclonal antibodies. The major challenge in cell line development for the production of recombinant biopharmaceuticals lies in generating and isolating rare high-producing stable clones, amongst thousands of low-producing or unstable clones, in a short period of time. One approach to accomplish this is to use the glutamine synthetase (GS) selection system, together with the GS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…It has been reported that CHO GS cell lines can produce higher titer after knockout of the GS genes. 46,47 We have reported that the titer can be improved by 25% after the temperature is shifted from 36.5°C to 32.0°C using the same CHO2 and Process B for the mAb production. 48 The doubled titer from Process B to C was attributed mainly to the more than 5-fold increase in SD, redesigned basal and feed media, feeding more nutrients, and an earlier temperature shift.…”
Section: Upstream Performancementioning
confidence: 99%
“…It has been reported that CHO GS cell lines can produce higher titer after knockout of the GS genes. 46,47 We have reported that the titer can be improved by 25% after the temperature is shifted from 36.5°C to 32.0°C using the same CHO2 and Process B for the mAb production. 48 The doubled titer from Process B to C was attributed mainly to the more than 5-fold increase in SD, redesigned basal and feed media, feeding more nutrients, and an earlier temperature shift.…”
Section: Upstream Performancementioning
confidence: 99%
“…Current fed-batch mAb manufacturing platforms are durable and robust and have not yet fully matured (Bielser et al 2018;Croughan et al 2015;Kelley et al 2018;Yongky et al 2019). From the 1980s to the 2010s, manufacturing titers improved from tens of mg/L to ≥ 3 g/L by cell line engineering (Lin et al 2019;Wurm 2013), media development (Galbraith et al 2018;Huang et al 2010;, and process control improvements (Tang et al 2020;Xu et al 2019;Yoon et al 2003) achieving higher cell specific productivities, increased peak VCDs, and prolonged high productivity durations (Kunert and Reinhart 2016;Li et al 2010;Rader and Langer 2015;Wurm 2004). Higher titers continue to be reported in recent literature (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The utilisation of mutant forms of GS with attenuated enzyme activity to derive antibody-secreting CHO-K1 cell lines with enhanced stability and higher productivity than cell lines derived with WT GS has recently been reported 31 . The first mutation analysed—R324C—was identified as a congenital mutation with less than 5% of WT enzyme activity, involved in ATP binding by GS 32 .…”
Section: Discussionmentioning
confidence: 99%